Strange the Dreamer - Laini Taylor (Little, Brown Books for Young Readers, 2017)
The dream chooses the dreamer, not the other way around--and Lazlo Strange, war orphan and junior librarian, has always feared that his dream chose poorly. Since he was just five years old, he's been obsessed with the mythic lost city of Weep, but it would take someone bolder than he to cross half the world in search of it. Then a stunning opportunity presents itself, in the form of a hero called the Godslayer and a band of legendary warriors, and he has to seize his chance or lose his dream forever.